Peran Ilmu Pengetahuan dalam Perkembangan Penelitian Ilmiah - Fadhilah Nur Oktaviani; Dina Maria Ulfa; Agung Winarno (Pusat Riset dan Inovasi Nasional, 2024)
Philosophy of science has a very important role in providing a conceptual basis for the advancement of science, especially through the study of ontology, epistemology, and axiology. This study aims to explore the contribution of science to the development of scientific research. By using a descriptive analysis method based on literature review, this study reveals that philosophy of science not only plays a role as a theoretical foundation, but also as a critical control tool for the application of science in social life. The results of the study suggest the importance of interdisciplinary integration and the development of science in the development of scientific research. Philosophy of science, with its comprehensive approach, is able to direct the development of science so that it remains relevant, ethical, and makes a positive contribution to civilization.